P1087HOME HEMODIALYSIS THROUGH THE YEARS. (6th June 2020) - Todorov Sakic, Verica; Djuric, Zivka; Djuric, Petar; Bulatovic, Ana; Tosic Dragovic, Jelena; Naumovic, Radomir; Dimkovic, Nada
Abstract: Background and Aims: Outcome of dialysis patients differ considerably across the globe and many studies confirmed that home-based treatments offer some advantages, not only in regard of quality of life but also regarding of patients' outcome. History of home hemodialysis (HOHD) in our country dates from 1971. and since that time many patients were treated with this dialysis modality. HOHD changed over the time together with general improving of dialysis techniques and we aimed to analyze the results of treatment of our population treated by HOHD during different time points. Method: We analyzed patients characteristics, dialysis and uremia-related complications and survival of patients on HOHD during three different time points: 2001. (No=70), 2011. (No=29) and 2019. (No=22). Results: The most frequent reason for ESRD in 2001, 2011 and 2019. was glomerulonephritis (48%, 45%, 36% respectively), followed by polycystic kidney disease 24% in 2011. and 36% in 2019. Diabetes mellitus (DM) was rarely cause of ESRD: in 2001. 2.1%; 4.5% in 2019. and none in 2011. In 2001. the patients were more frequently treated using high flux membranes (HF) as compared to HDF (87.1% vs.12.9%), and through years this changed in favor of HDF (48% vs. 52% in 2011, and 13.6% vs. 86.4% in 2019). Anti HCV prevalence was 27.4%, 38%, 27%, in 2001, 2011. and 2019. respectively. Anemia status was better controlled in recent years revealed by Hb level: 10.5±2.0 g/dl in 2001, 12.1±1.6 in 2011. and 11.9±2.3 in 2019. with almost similar percentage of patients treated with ESA (31%, 28% and 36% respectively). In 2001, parathyroid hormone level (iPTH) was 379±236 pmol/l and only 20% of patients underwent parathyroidectomy while in 2011. and in 2019. parathyroidectomy was performed in 69% and 59% of patients respectively. Therefore, in 2011. and in 2019. mean iPTH level was 33.8±48.5 and 40±46.2pmol/l respectively. Kaplan-Mayer analysis confirmed ten-year survival of 42% for period 1982-2001, and the most frequent reasons for death were infection and cardiovascular diseases. During the period 2011. to 2019., ten-year survival was 88% and cardiovascular diseases led to death in most of the cases. Conclusion: our results have shown that HOHD treatment improved through the years considering patients' survival, anemia status and secondary hyperparathyroidism treatment. Apart from HDF, the other factors have to be taken into consideration.